2004
DOI: 10.1159/000076548
|View full text |Cite
|
Sign up to set email alerts
|

Glucoreceptors Located Inside the Blood-Brain Barrier Mediate Hypoglycemia-Induced LH Inhibition in Man

Abstract: Objective: To establish the role of hyperinsulinemia and hypoglycemia during the insulin tolerance test (ITT) in the regulation of luteinizing hormone (LH) secretion and the location with respect to the blood-brain barrier (BBB) of the glucosensitive areas controlling LH release. Methods: The LH-secretory pattern during an ITT (0.15 IU/kg body weight) was evaluated in 8 normal men during infusion with normal saline (control test), glucose or fructose. Results: lnsulin-induced hypoglycemia produced a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This hypothesis is supported by recent data of Coiro et al. , who found that the LH decrease during insulin‐induced hypoglycaemia is generated by glucosensitive areas located inside the blood–brain barrier 30 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This hypothesis is supported by recent data of Coiro et al. , who found that the LH decrease during insulin‐induced hypoglycaemia is generated by glucosensitive areas located inside the blood–brain barrier 30 …”
Section: Discussionsupporting
confidence: 74%
“…This hypothesis is supported by recent data of Coiro et al, who found that the LH decrease during insulin-induced hypoglycaemia is generated by glucosensitive areas located inside the blood-brain barrier. 30 Finally, the finding of normalized sex hormone levels in the morning of day 2 after two episodes of hypoglycaemia needs to be discussed as it seems to have some clinical relevance for type 1 diabetic patients. A large number of these patients exhibit hypoglycaemic episodes, 31 especially during the night-time, 32,33 which presumably decreases serum LH and testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-induced hypoglycemia is a highly quantifiable and reproducible stressor that inhibits LH secretion to which animals, including humans, do not habituate. 173,181,182 In addition to insulin-induced hypoglycemia, acute glucoprivation by 2-deoxyglucose administration profoundly suppresses pulsatile LH secretion in the rat. 107,179,180 Affects on LH pulse amplitude are also reported for the rat 177 and ewe, 178 although not in the monkey.…”
Section: Metabolic Stressorsmentioning
confidence: 99%
“…It was originally suspected that these "glucoreceptors" were located in the CNS and probably in the hypothalamus (Mayer, 1956). As time passed, it was suspected and later demonstrated (Shiota and Magnuson, 2008) that these receptors were in fact located in hepatic circulation (Niijima, 1969;Russek & Grinstein, 1974;Russek, 1981), the gastrointestinal tract (Mei, 1978), the causal hind brain (Ritter, 1981), and more recently the blood brain barrier (BBB) (Coiro, 2004). The decrease or increase in the utilization of glucose described above then in turn stimulates either satiety or hunger respectively along with a variety of other factors.…”
Section: Appetite Parametersmentioning
confidence: 99%